Dinamika Kewarganegaraan Digital dan Pola Penyebaran Hate Speech di Media Sosial: Studi Kasus di Kalangan Remaja Indonesia: Dynamics of Digital Citizenship and Patterns of Spreading Hate Speech on SocialMedia: Case Study among Indonesian Teenagers - Ahmad Muhamad Mustain Nasoha; Elsya Novitasari Anggraini; Ziadatul Latifah; Erma Nur Fitriyani (Litera Academica Publishing, 2025)
Along with the rapid adoption of social media, the digital space has become a new arena for social interaction, particularly among Indonesian youth. However, this development has also brought serious challenges, one of which is the phenomenon of hate speech. This study aims to analyze the dynamics of digital citizenship and the patterns of hate speech dissemination on social media, focusing on a case study among adolescents. Using a qualitative approach with a case study method, data were collected through in-depth interviews with several teenagers, online participatory observation, and content analysis of conversations on social media platforms. The results of the study show that the patterns of hate speech dissemination among adolescents vary, ranging from discriminatory comments, identity-based mockery, to cyberbullying. These patterns are often driven by psychological and social factors, such as anonymity, peer pressure, lack of understanding of digital ethics, and the influence of provocative viral content. The study also found a gap between adolescents’ theoretical understanding of digital citizenship and their daily practices on social media. They tend to perceive the digital space as a consequence-free arena, which reduces their sense of moral responsibility. Thus, this research concludes that the phenomenon of hate speech among adolescents is not merely a technical issue but a reflection of the challenges in building a substantive awareness of digital citizenship. The implication is that a holistic approach involving formal education, parental roles, and platform regulation is needed to equip teenagers with strong digital literacy and a responsible expression ethic.